Teddy bears and tigers: How renewable energy can revitalise local communities. (September 2014) - Callaghan, George; Williams, Derek
In recent years, in Scotland, there has been significant policy and academic interest in community ownership and in renewable energy. This paper draws these two together and investigates the economic and social impact of community ownership of renewable energy projects. The researchers gained access to the project database of Community Energy Scotland to gather primary and secondary data from a number of large-scale revenue-generating and small-scale community energy projects. The paper looks at the economic impact of community participation in renewable energy schemes and examines how this is used to stimulate local economies and societies. Also emerging from the data is the social impact of community renewables, particularly the nurturing of new networks and the improvement in community confidence. The paper also discusses the challenges and policy implications of community-owned renewables. These include funding, the relationship between the level of community ownership and local economic impact and the need for further community empowerment.